Feasibility, appropriateness and meaningfulness analysis of the Sunfrail Tool to the European Portuguese population during cross-cultural adaptation process - Cardoso, A. F.; Bobrowicz-Campos, E.; Couto, F.; Cardoso, D.; Barata, A.; Apóstolo, J. (International Journal of Evidence-Based Healthcare, 2019)
Frailty is an age-related condition characterized by increased vulnerability to negative outcomes. To enable informed decision-making and implementation of individually tailored practices for frailty management, it is necessary to develop screening tools that cover different domains of individual functioning, reliably predict future adverse outcomes and are generalizable to healthcare settings other than primary care. The Sunfrail Tool, an easy-to-use nine-item instrument, seems to meet all these requirements. The current study aimed to perform a cross-cultural adaptation of the Sunfrail Tool for the European Portuguese population and to perform the feasibility, appropriateness and meaningfulness analyses of the Sunfrail Tool Portuguese version. Methods: The process of cross-cultural adaptation was conducted in four-phases (translation, synthesis, back translation and creation of consensual version). To reinforce the content validity, the additional analysis on feasibility, appropriateness and meaningfulness were conducted with end-users (older adults, informal caregivers and health and social care professionals). Results: The frailty concept was considered suitable for the European Portuguese population. A consensus version was reached by an expert panel after considering the results of two forward and two back-translations. This prefinal version was endorsed to the first author of the original version of the instrument, as recommended by international guidelines. The content validation performed by healthcare professionals (n ¼ 7), patients (n ¼ 18) and informal caregivers (n ¼ 3) showed that the Sunfrail Tool was moderately comprehensible and ambiguous. Five items required changes for cultural adaptation. Conclusion: The Sunfrail Tool seems to be a promising instrument for the early identification of frailty to be used in the European Portuguese context to inform clinical decisions on preventive responses. However, to enable identification of frail and nonfrail individuals with this tool and ensure effectiveness on pathways activation for frailty management, there is a need to define cut-off points. Guidelines supporting the interview process are also desirable.